(X ^ 3 + 4x ^ 2 + 6x + 4) -: (x + 2) nedir?

(X ^ 3 + 4x ^ 2 + 6x + 4) -: (x + 2) nedir?
Anonim

Cevap:

# (X ^ 3 + 4x ^ 2 + 4 + 6 x) = (x ^ 2 + 2 + 2x) (x + 2) #

Açıklama:

Yapımı #f (x) = x ^ 3 + 4x ^ 2 + 6x + 4 # Biz biliyoruz ki # X = -2 # çünkü bu denklemin kökeni #f (-2) = 0 #. Yani #f (x) = q (x) (x + 2) #. Şimdi poz #Q (x) = ax ^ 2 + bx + c # ve denkleme #f (x) q (X) (x + 2) = 0 # sahibiz:# (1-a) x ^ 3 + (4-2a-b) x ^ 2 + (6-2b-c) x + 4-2c = 0 #. Bu ilişki herkes için boş olmalı # X # bu yüzden elde ediyoruz: #Q (x) = x ^ 2 + 2x + 2 #